El origen de la cultura en Kant. El hiato entre la vida y la moral - Sánchez Madrid, Nuria (2018)
“The Origin of Culture in Kant. The Hiatus Between Life and Morality”. This paper attempts to investigate the meaning and function that culture plays as an existential activity in the work of Kant, driving special attention to the Critique of Judgment and to the materials furnished by the Anthropology from a pragmatic point of view, having as key goal the survey of its anthropological and social sources. From this perspective, I intend first to argue that the Kantian analysis of life and the intrinsic nihilism recognized in it largely explain the origin of the concept of culture in Kant, basically understood as a set of practices that allow human beings to extract some teleological performance from time passing. Secondly, I will discuss the phenomenon of entertainment as an anthropological key subject to deepen in the necessity of the advent of culture in human society. Both purposes belong to what I consider a Kantian genealogy of culture, adequate for the interpretation of the link between the theoretical and practical use of reason.